Nickel element doped resorcinol-formaldehyde resin photocatalyst as well as preparation method and application thereof

By introducing nickel elements as oxygen adsorption sites in resorcinol-formaldehyde resin, the nickel-doped resorcinol-formaldehyde resin photocatalyst is solved, and the problem of the existing photocatalysts requiring additional sacrificial agent is achieved, and high efficiency is achieved , low-cost hydrogen peroxide production.

CN119425788AActive Publication Date: 2025-02-14JIANGSU UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411565678.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

Existing photocatalysts require additional sacrificing agents in the process of producing hydrogen peroxide (H2O2), which increases costs and complexes mechanism evaluation. At the same time, the element doping method has problems such as environmental pollution and high costs.

Method used

Nickel element is introduced as the oxygen adsorption site in resorcinol-formaldehyde resin, and nickel is introduced during the alkali catalytic condensation and polymerization process through nickel acetate as the nickel source to form a nickel-doped resorcinol-formaldehyde resin photocatalyst.

Benefits of technology

Significantly improves photocatalytic performance, enhances oxygen adsorption and activation capabilities, promotes the conversion of intermediates to hydrogen peroxide, improves the selectivity and yield of hydrogen peroxide, and reduces production costs without the need for additional sacrificial agents. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425788A_ABST
    Figure CN119425788A_ABST
Patent Text Reader

Abstract

The invention discloses a nickel-doped resorcinol-formaldehyde resin photocatalyst and a preparation method and application thereof.According to the photocatalyst, the adsorption capacity of the surface of resorcinol-formaldehyde resin to oxygen is remarkably adjusted through nickel metal active sites, oxygen dissociation is inhibited, the conversion process of an intermediate to hydrogen peroxide is promoted, and the yield of hydrogen peroxide is increased. The selectivity of hydrogen peroxide is enhanced, in-situ decomposition of hydrogen peroxide is inhibited, and the performance of producing hydrogen peroxide is high and stable; the method is low in production cost, simple and convenient in one-step preparation process, easy to implement in practical application, low in product toxicity, mild in application environment and free of sacrificial agents, can efficiently produce hydrogen peroxide in purified water only through visible light irradiation, and has great application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a photocatalyst, in particular to a nickel-doped resorcinol-formaldehyde resin photocatalyst, and also to a preparation method and application of the photocatalyst. Background Art

[0002] Hydrogen peroxide (H 2 O 2 ) is one of the world's top 100 chemicals and can be used not only as an oxidant in organic synthesis, textile bleaching and wastewater treatment, but also as a liquid fuel that can be stored and transported in fuel cells. 2 O 2 The industrial production of H2O2 mainly relies on the anthraquinone process, which not only requires strict production conditions, but also has environmental problems caused by a large number of chemical byproducts. Therefore, it is necessary to develop a new type of H2O2 that is efficient and environmentally friendly. 2 O 2 Production technology is an urgent need.

[0003] Using water and oxygen as raw materials, H 2 O 2 The traditional H 2 O 2 The production method provides an innovative alternative method. 2 O 2 It involves two half reactions: the two-electron oxygen reduction reaction (ORR) involving electrons in the semiconductor conduction band and the water oxidation reaction (WOR) involving holes in the valence band. Scholars have modified photocatalysts to couple the ORR reaction and the WOR reaction to the photocatalytic generation of H 2 O 2 In the process of photocatalysis, sacrificial agents are often used to improve the performance of photocatalysis. However, the additional use of sacrificial agents not only increases the cost but also brings challenges to elucidating the mechanism and evaluating the catalytic efficiency.

[0004] Efficient photocatalytic ORR reaction to generate H 2 O 2 The adsorption and activation of oxygen on the catalyst surface significantly affect the progress of the reaction, requiring a synergistic interaction between electrons and oxygen. Photocatalytic activity is believed to be the cumulative result of surface reactions between active sites on the catalyst and reactants. Therefore, constructing active sites within the catalyst that regulate oxygen behavior is a viable strategy to enhance photocatalytic activity and develop efficient photocatalysts.

[0005] Resorcinol-formaldehyde resin (RF) is a low-cost, low-toxic and easy-to-synthesize organic polymer that has attracted widespread attention in the field of photocatalysis. However, RF resins exhibit low photocatalytic performance due to the problem of easy recombination of photogenerated electrons and holes. Element doping has been widely reported as an effective means to adjust the band structure and alleviate the problem of electron-hole pair recombination. Element doping is used to improve the catalyst structure and 2 O 2 The introduction of active sites capable of modulating the action of oxygen during production is a promising research avenue for achieving efficient photocatalysts.

[0006] Among the current element doping methods, the preparation process of doping with non-metallic elements such as carbon, oxygen, sulfur, phosphorus, etc. is usually complicated, and the preparation process will cause certain environmental pollution. Doping with alkali metal elements such as potassium and sodium will usually destroy the original morphology of the material. Doping with rare earth metals and precious metals will also greatly increase the preparation cost of the material. Other modification methods for resorcinol-formaldehyde resin, such as introducing other organic groups or compounding with other materials, although these modification methods improve their photocatalytic properties, are usually accompanied by harsh and complex synthesis conditions and high preparation costs, making them difficult to apply in practice. Summary of the invention

[0007] Purpose of the invention: The purpose of the present invention is to provide a nickel-doped resorcinol-formaldehyde resin photocatalyst that introduces nickel sites as oxygen adsorption sites in the resorcinol-formaldehyde resin to greatly improve the photocatalytic performance, and also provide a method for preparing the above-mentioned photocatalyst and its application in photocatalytic efficient production of hydrogen peroxide.

[0008] Technical solution: The present invention discloses a nickel-doped resorcinol-formaldehyde resin photocatalyst. The photocatalyst is a spherical structure formed by nickel elements dispersedly distributed on the surface of the resorcinol-formaldehyde resin. The photocatalyst is obtained by introducing a nickel source during the base-catalyzed polycondensation process of the resorcinol-formaldehyde resin.

[0009] Wherein, the molar ratio of the nickel element to the resorcinol-formaldehyde resin is 7:0.0001-0.0007.

[0010] The method for preparing the nickel-doped resorcinol-formaldehyde resin photocatalyst comprises the following steps:

[0011] (1) dispersing resorcinol, formaldehyde solution, ammonia solution and nickel acetate solution in water and stirring to form a suspension;

[0012] (2) subjecting the suspension obtained in step (1) to a hydrothermal reaction;

[0013] (3) After cooling to room temperature, the product obtained by the reaction is centrifuged and washed, and then vacuum dried to obtain a nickel-doped resorcinol-formaldehyde resin photocatalyst.

[0014] Wherein, in step (1), the mass ratio of resorcinol, formaldehyde solution, ammonia water, nickel acetate and water is 0.8:1.2:0.4:0.25×10 -4 ~1.75×10 -4 :60.

[0015] Wherein, in step (1), the stirring is carried out by using a magnetic stirrer at a rate of 500 to 600 r / min.

[0016] Wherein, in step (2), the hydrothermal reaction is carried out at a temperature of 230-260° C. and for a time of 20-26 h; preferably at 250° C. and for 24 h.

[0017] Wherein, in step (3), the washing solvents used are water and ethanol, and the vacuum drying temperature is 50-80°C and the time is 12-24h, preferably 60°C and 12h.

[0018] The nickel-doped resorcinol-formaldehyde resin photocatalyst can also be used to produce hydrogen peroxide under visible light catalysis.

[0019] Principle of the invention: The nickel-doped resorcinol-formaldehyde resin photocatalyst of the present invention introduces nickel sites as oxygen adsorption sites into the resorcinol-formaldehyde resin to greatly improve the photocatalytic performance; nickel acetate is used as a nickel source to be introduced into the simple base-catalyzed condensation synthesis process of the resorcinol-formaldehyde resin, and nickel elements are introduced into the polymerization process of the benzene-type and quinone-type π stacking structures, thereby forming a low-cost, low-toxic nickel-doped resorcinol-formaldehyde resin.

[0020] Compared with elements such as iron and copper that are easy to react with hydrogen peroxide, nickel has low cost and strong improvement in photocatalytic performance; doping with low-cost transition metal element nickel can not only improve light absorption, narrow the band gap, accelerate charge migration, but also save the cost of production and manufacturing. Therefore, the present invention chooses to introduce low-cost transition metal element nickel as an active site for adsorbing oxygen to participate in photocatalytic production of hydrogen peroxide. The introduction of nickel metal sites regulates the oxygen adsorption capacity of the surface of resorcinol-formaldehyde resin, enhances the effectiveness of oxygen to the catalyst surface and participating in the production of hydrogen peroxide, and the introduction of nickel elements realizes effective regulation of the band structure of resorcinol-formaldehyde resin, making it more thermodynamically conducive to photocatalytic production of hydrogen peroxide. When there are too few nickel metal sites in the resorcinol-formaldehyde resin, the adsorption effect of oxygen is poor. Excessive nickel sites will cover the active sites for producing hydrogen peroxide in the resorcinol-formaldehyde resin and hinder the production of hydrogen peroxide. The appropriate amount of nickel metal sites not only inhibits the dissociation of oxygen and enhances the selectivity, promoting the conversion of intermediates into hydrogen peroxide; it also effectively inhibits the in situ decomposition of photocatalytically generated hydrogen peroxide on the surface of the resorcinol-formaldehyde resin catalyst, further improving the yield of hydrogen peroxide.

[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The photocatalyst of the present invention significantly regulates the adsorption capacity of the surface of resorcinol-formaldehyde resin for oxygen through the nickel metal active site, inhibits the dissociation of oxygen, promotes the conversion process of the intermediate into hydrogen peroxide, enhances the selectivity of hydrogen peroxide, and inhibits the in-situ decomposition of hydrogen peroxide, and the performance of producing hydrogen peroxide is high and stable; (2) The production cost of the photocatalyst of the present invention is low, the one-step preparation process is simple and convenient, and it is easy to implement in practical application; (2) Nickel-doped resorcinol-formaldehyde resin has low toxicity, mild application environment, no sacrificial agent is required, and hydrogen peroxide can be efficiently produced in pure water only by visible light irradiation. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The scanning electron microscope (SEM) and corresponding element distribution of RF of Example 1 and NiRF-5 of Example 3, wherein a is the SEM image of RF, b is the SEM image of NiRF-5, c is the C element distribution in NiRF-5, d is the O element distribution in NiRF-5, and e is the Ni element distribution in NiRF-5;

[0023] Figure 2 The X-ray diffraction (XRD) patterns of the products of the embodiments and comparative examples;

[0024] Figure 3The full X-ray photoelectron spectroscopy (XPS) spectra of RF and NiRF-5 and the high-resolution XPS spectra of C, O and Ni elements, wherein a is the full XPS spectra of RF and NiRF-5, b is the high-resolution XPS spectra of C element of RF and NiRF-5, c is the high-resolution XPS spectra of O element of RF and NiRF-5, and d is the high-resolution XPS spectra of Ni element of NiRF-5;

[0025] Figure 4 Fourier transform infrared analysis spectra (FT-IR) of RF and NiRF-5;

[0026] Figure 5 UV-visible diffuse reflectance spectra (a) and VB-XPS spectra (b) of RF and NiRF-5;

[0027] Figure 6 The band structures of RF and NiRF-5;

[0028] Figure 7 The hydrogen peroxide yields of the products of the examples and comparative examples under visible light;

[0029] Figure 8 is the hydrogen peroxide production rate of RF and NiRF-5 under visible light;

[0030] Fig. 9 is the hydrogen peroxide production of RF and NiRF-5 in different atmospheres under visible light;

[0031] Fig.10 is the hydrogen peroxide yield of RF and NiRF-5 in saturated oxygen under visible light;

[0032] Fig.11 is the hydrogen peroxide decomposition curve of RF and NiRF-5;

[0033] Fig.12 DMPO-·O for RF and NiRF-5 2 - ESR spectrum of the signal;

[0034] Fig.13 Temperature programming for RF and NiRF-5 2 Desorption (TPD-O 2 )atlas. DETAILED DESCRIPTION

[0035] The technical scheme of the present invention is further described below in conjunction with the examples. The test materials used in the examples can all be purchased through conventional channels.

[0036] Example 1

[0037] The nickel-doped resorcinol-formaldehyde resin photocatalyst of the present invention comprises the following steps:

[0038] (1) 792 mg of resorcinol, 1080 μL of formaldehyde solution, 460 μL of ammonia solution, and 0.1 mL of nickel acetate solution (1 mM) were dispersed in 60 mL of deionized water and stirred at 500-600 rpm with a magnetic stirrer at room temperature to form a suspension;

[0039] (2) The formed suspension was transferred to a polytetrafluoroethylene-lined reactor and reacted at 250° C. for 24 h;

[0040] (3) After cooling to room temperature, the product was washed with water and ethanol, and dried in a vacuum oven at 60 °C for 12 h to obtain a reddish-brown nickel-doped resorcinol-formaldehyde resin powder, which was labeled as NiRF-1.

[0041] Example 2

[0042] Compared with Example 1, the content of nickel acetate solution was changed:

[0043] (1) Preparation of nickel-doped resorcinol-formaldehyde resin: 792 mg of resorcinol, 1080 μL of formaldehyde solution, 460 μL of ammonia solution, and 0.3 mL of nickel acetate solution (1 mM) were dispersed in 60 mL of deionized water, and stirred at 500-600 r / min with a magnetic stirrer at room temperature to form a suspension;

[0044] (2) The formed suspension was transferred to a polytetrafluoroethylene-lined reactor and reacted at 250° C. for 24 h;

[0045] (3) After cooling to room temperature, the product was washed with water and ethanol, and dried in a vacuum oven at 60 °C for 12 h to obtain a reddish-brown nickel-doped resorcinol-formaldehyde resin powder, which was labeled as NiRF-3.

[0046] Example 3

[0047] Compared with Example 1, the content of nickel acetate solution was changed:

[0048] (1) Preparation of nickel-doped resorcinol-formaldehyde resin: 792 mg of resorcinol, 1080 μL of formaldehyde solution, 460 μL of ammonia solution, and 0.5 mL of nickel acetate solution (1 mM) were dispersed in 60 mL of deionized water, and stirred at 500 to 600 r / min with a magnetic stirrer at room temperature to form a suspension;

[0049] (2) The formed suspension was transferred to a polytetrafluoroethylene-lined reactor and reacted at 250° C. for 24 h;

[0050] (3) After cooling to room temperature, the product was washed with water and ethanol, and dried in a vacuum oven at 60 °C for 12 h to obtain a reddish-brown nickel-doped resorcinol-formaldehyde resin powder, which was labeled as NiRF-5.

[0051] Example 4

[0052] Compared with Example 1, the content of nickel acetate solution was changed:

[0053] (1) Preparation of nickel-doped resorcinol-formaldehyde resin: 792 mg of resorcinol, 1080 μL of formaldehyde solution, 460 μL of ammonia solution, and 0.7 mL of nickel acetate solution (1 mM) were dispersed in 60 mL of deionized water, and stirred at 500 to 600 r / min with a magnetic stirrer at room temperature to form a suspension;

[0054] (2) The formed suspension was transferred to a polytetrafluoroethylene-lined reactor and reacted at 250° C. for 24 h;

[0055] (3) After cooling to room temperature, the product was washed with water and ethanol, and dried in a vacuum oven at 60 °C for 12 h to obtain a reddish-brown nickel-doped resorcinol-formaldehyde resin powder, which was labeled as NiRF-7.

[0056] Comparative Example 1

[0057] The method for preparing resorcinol-formaldehyde resin, compared with Example 1, does not add nickel acetate, and specifically comprises the following steps:

[0058] (1) Preparation of resorcinol-formaldehyde resin: 792 mg of resorcinol, 1080 μL of formaldehyde solution, and 460 μL of ammonia solution were dispersed in 60 mL of deionized water, and stirred at 500-600 r / min with a magnetic stirrer at room temperature to form a suspension.

[0059] (2) The formed suspension was transferred to a polytetrafluoroethylene-lined reactor and reacted at 250° C. for 24 h.

[0060] (3) After cooling to room temperature, the product was washed with water and ethanol and dried in a vacuum oven at 60 °C for 12 h to obtain a reddish brown resorcinol-formaldehyde resin powder, which was marked as RF.

[0061] like Figure 1As shown, the RF of comparative example 1 and the NiRF-5 of example 3 were characterized by scanning electron microscopy (SEM): it can be seen that both RF and NiRF-5 showed a uniform spherical morphology with a diameter of about 400nm. The introduction of nickel ions did not affect the uniform spherical shape of the RF resin, and no obvious aggregation of nickel nanoparticles occurred, indicating that the incorporation of nickel ions did not interfere with the polymerization process of the RF resin, nor did it affect its size and morphology. In addition, the element distribution image confirmed the uniform distribution of C, O and Ni elements in the NiRF-5 resin. These findings verify the incorporation of nickel elements and their uniform dispersion in the RF resin, thereby confirming the successful preparation of nickel-doped RF resin.

[0062] like Figure 2 The products obtained in all the examples and comparative examples were characterized by X-ray diffraction (XRD): RF and NiRF-5 resins both showed broad diffraction peaks at about 2θ = ~20°, indicating the (002) crystal plane of graphitic carbon, indicating that both RF and NiRF-5 resins belong to the π stacking of donor-acceptor pairs of aromatic compounds. The diffraction peak of NiRF shifted slightly to a higher angle, and the magnitude of this shift increased with the increase of the doping content. In addition, no obvious nickel metal peak appeared, which means that the incorporation of nickel does not produce any new crystalline phase. These findings in turn confirm the successful synthesis of nickel-doped RF resin.

[0063] like Figure 3 X-ray photoelectron spectroscopy was performed on RF and NiRF-5: It can be clearly observed from the full XPS spectrum that both C and O elements exist in RF and NiRF-5, while the signal peak of Ni element in NiRF-5 is relatively weak due to the low doping content of Ni element. Each element was analyzed in detail by high-resolution XPS spectra of C, O and Ni elements. The C1s high-resolution XPS spectra of RF and NiRF-5 can be deconvoluted into three different main peaks, located at 284.6, 286.0 and 288.1 eV, corresponding to C=C, CO and C=O bonds, respectively. In the high-resolution XPS spectrum of O1s, the introduction of Ni into RF resin leads to the appearance of a peak at 530.8 eV, which is attributed to the appearance of CO-Ni bond, indicating that nickel and RF resin are connected through CO-Ni bond. In addition, in the high-resolution XPS spectrum of Ni 2p of NiRF-5, the presence of Ni 2p3 / 2 and Ni 2p1 / 2 signals can be observed, which fully confirms that the Ni element is successfully doped into the RF resin.

[0064] like Figure 4 Fourier transform infrared spectra of RF and NiRF-5 were used to characterize the RF and NiRF-5 resins. -13005 and 1399 cm-1 show vibration signals, corresponding to the υO-H and υC-O stretching vibrations of resorcinol and hydroxymethyl, respectively. -1 The peak at 1619 cm is attributed to the υC-H and σC-H stretching vibrations of the methylene group, while the peak at 1619 cm -1 The peak at 512 cm is attributed to the υC=C stretching vibration of the aromatic ring. In addition, in the infrared spectrum of NiRF-5 resin, a new peak of Ni-O signal appears at 512 cm -1 The presence of Ni-O bonds will adjust the electronic structure of the material and optimize its adsorption capacity for oxygen intermediates, while providing a charge transfer pathway and reducing the energy barrier required for charge transfer.

[0065] like Figure 5 UV-Vis diffuse reflectance and VB-XPS characterization of RF and NiRF-5: The optical properties of RF and NiRF-5 resins were analyzed using UV-Vis diffuse reflectance spectra. The successful doping of Ni element caused the intrinsic absorption edge of RF resin to red-shift, enhancing its light absorption ability in the visible spectrum. In addition, the band gap values ​​of RF and NiRF-5 resins were determined to be 2.10 and 2.06 eV, respectively. Based on these band gap values, the band structure was further calculated and analyzed using VB-XPS testing.

[0066] like Figure 6 The band structures of RF and NiRF-5 were analyzed: In RF resin, the benzene-type and quinone-type units are used as the valence band (VB) and conduction band (CB), respectively, and the π-stacked hybrid donor-acceptor pairs for electron transitions lead to the production of this narrow bandgap semiconductor. The band gap is further narrowed after Ni doping, and the band position moves toward a more negative potential. The suitable band structure of NiRF not only fully meets the thermodynamic conditions for the photocatalytic oxygen reduction to produce hydrogen peroxide, but its negative VB also has a positive effect on the reduction ability of photogenerated electrons.

[0067] The products obtained in all the examples and comparative examples were subjected to visible light photocatalysis to generate H 2 O 2 Yield test:

[0068] The photocatalytic H generation was evaluated under visible light using a multi-channel photoreactor (Pefectlight PCX-50C, Beijing). 2 O 2 Production performance, where visible light (λ>400nm) was provided by a light board equipped with a 10W LED lamp. During the experiment, 20mg of the catalyst was initially added to 30mL of deionized water to form a uniform suspension. During light irradiation, 2mL of the suspension sample was periodically taken out of the reaction cell and the photocatalyst powder was removed by centrifugation. The collected solution was diluted 10 times before iodine titration. H was then measured using iodine titration2 O 2 The concentration of H is usually determined by complexing a certain volume of fluorescent reagent (0.1 M potassium hydrogen phthalate and 0.4 M potassium iodide aqueous solution) with the reaction system. 2 mL of the diluted solution sample was collected and 1 mL of the fluorescent reagent was added to each sample. After a reaction period of 30 minutes, the absorbance at 350 nm was measured using a UV-Vis spectrophotometer to estimate the H concentration during each reaction. 2 O 2 concentration.

[0069] The results are as follows Figure 7 As shown, all samples showed enhanced photocatalytic H conversion in pure water compared with pure RF resin. 2 O 2 Among them, NiRF-5 showed the highest photocatalytic performance (720 μM) under the condition of no additional oxygen, which significantly exceeded the pure phase RF resin (497 μM).

[0070] Visible light photocatalytic generation of H 2 O 2 Yield test:

[0071] The yield is calculated based on the output. Figure 8 As shown, the photocatalytic H 2 O 2 The yield is also 1.45 times higher than that of pure RF resin, indicating that nickel doping significantly improves the generation of H 2 O 2 ability.

[0072] RF and NiRF-5 were subjected to H2O in different atmospheres under visible light. 2 O 2 Yield test:

[0073] The ambient atmosphere during the reaction has an important effect on the photocatalytic generation of H by RF resin. 2 O 2 The process has a great influence on the H 2 O 2 The production performance was tested. The solution was aerated for half an hour before the yield test, and then the light was turned on to test the photocatalytic performance.

[0074] The results are as follows Fig. 9 As shown, in saturated N 2 In the atmosphere, both RF and NiRF-5 resins showed low H 2 O 2 The results show that both of them mainly produce H through ORR pathway. 2 O 2 In saturated O2 In the atmosphere, RF and NiRF-5 photocatalyzed the generation of H 2 O 2 The performance of RF resin was significantly enhanced, with the values ​​of 0.61 and 1.27 mM, respectively, which indicated that the ORR reaction was significantly 2 O 2 Play a leading role in the production process.

[0075] RF and NiRF-5 were subjected to H in saturated oxygen under visible light. 2 O 2 Yield test:

[0076] The yield is calculated based on the output. Fig.10 As shown, the photocatalytic H 2 O 2 The production rate reaches 31.75mM / g / h, which is 2.08 times that of pure RF.

[0077] The hydrogen peroxide decomposition process was tested on RF and NiRF-5:

[0078] In H 2 O 2 During the production process, formation and decomposition occur simultaneously. Therefore, RF and NiRF-5 were subjected to H 2 O 2 Decomposition test. 20 mg of catalyst powder was mixed with 100 mL of H at a certain concentration in the dark. 2 O 2 (1mmol / L) and measured H 2 O 2 The residual concentration of H 2 O 2 Decomposition experiment. According to the above method, the corresponding H 2 O 2 Concentration, H 2 O 2 The decomposition rate is calculated as follows:

[0079] H 2 O 2 Decomposition rate (%) = (1-C / C 0 )×100%

[0080] Among them C 0 Yes H 2 O 2 The initial concentration of H 2 O 2 concentrations at different times.

[0081] The results are as follows Fig.11 As shown, NiRF-5 exhibited lower H2 O 2 The decomposition rate indicates that H 2 O 2 The decomposition on NiRF-5 resin was relatively slow, which was beneficial to the generation of H 2 O 2 accumulation.

[0082] like Fig.12 The ESR spectra of RF and NiRF-5 showed that DMPO-·O 2 - The presence of the signal was characterized by electron spin resonance (ESR) testing of the photocatalytic H 2 O 2 Key intermediates in the production process 2 - There was no obvious peak under dark conditions, but after 20 minutes of visible light irradiation, NiRF-5 showed stronger DMPO-·O than RF resin. 2 - Signal strength. This fully proves that 2 - As a key intermediate in the indirect two-step single-electron ORR reaction, it participates in the photocatalytic H 2 O 2 In addition, under the same illumination time, the intermediate product of NiRF-5·O 2 - The high signal intensity indicates that the photocatalytic generation of H 2 O 2 The potential is greater.

[0083] like Fig.13 RF and NiRF-5 were subjected to temperature programming 2 Desorption (TPD-O 2 ) Characterization: Photocatalytic ORR reaction in RF resin produces H 2 O 2 In the process, O 2 Reach the surface of the RF resin and effectively utilize the H generated 2 O 2 Compared with RF, NiRF-5 showed a larger peak area, indicating that NiRF-5 has a stronger ability to 2 The superior adsorption capacity of RF resin indicates that nickel doping promotes its adsorption of O 2 The adsorption and activation of 2 O 2 performance.

Claims

1. A nickel-doped resorcinol-formaldehyde resin photocatalyst, characterized in that: The photocatalyst is a spherical structure formed by nickel elements dispersed on the surface of the resorcinol-formaldehyde resin, which is obtained by introducing a nickel source during the base-catalyzed polycondensation of the resorcinol-formaldehyde resin. The introduced nickel elements are connected with hydroxyl groups to form Ni-O bonds.

2. The photocatalyst according to claim 1, characterized in that The molar ratio of the nickel element to the resorcinol-formaldehyde resin is 7:0.0001-0.0007.

3. A method for preparing the nickel-doped resorcinol-formaldehyde resin photocatalyst according to claim 1, characterized in that: The following steps are involved: (1) dispersing resorcinol, formaldehyde solution, ammonia solution and nickel acetate solution in water and stirring to form a suspension; (2) subjecting the suspension obtained in step (1) to a hydrothermal reaction; (3) After cooling to room temperature, the product obtained by the reaction is centrifuged and washed, and then vacuum dried to obtain a nickel-doped resorcinol-formaldehyde resin photocatalyst.

4. The method according to claim 3, characterized in that: In step (1), the mass ratio of resorcinol, formaldehyde solution, ammonia water, nickel acetate and water is 0.8:1.2:0.4:0.25×10 -4 ~1.75×10 -4 :

60.

5. The method according to claim 3, characterized in that: In step (1), the stirring is carried out using a magnetic stirrer at a rate of 500 to 600 r / min.

6. The method according to claim 3, characterized in that: In step (2), the hydrothermal reaction is carried out at a temperature of 230 to 260° C. and for a time of 20 to 26 hours.

7. The method according to claim 3, characterized in that: In step (3), the washing solvents used are water and ethanol, and the vacuum drying temperature is 50 to 80° C. and the time is 12 to 24 hours.

8. Use of the nickel-doped resorcinol-formaldehyde resin photocatalyst according to claim 1 to produce hydrogen peroxide under visible light catalysis.

Citation Information

Patent Citations

  • D-A type phenolic resin photocatalyst as well as preparation method and application thereof

    CN115121290A

  • Synthetic method and application of heteroatom-doped phenolic resin microspheres

    CN116493047A

  • 3-hydroxythiophenol-formaldehyde resin as well as preparation method and application thereof

    CN116640277A